2020
DOI: 10.1016/j.psj.2019.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four nonlinear growth models in Creole chickens of Mexico

Abstract: Animal growth is a complex and dynamic process that involves physiological and morphological changes from hatching to maturity. It is defined as the increase in body size per time unit. Mathematical functions, called growth models, have been used to explain growth patterns. The aim of this study was to compare the Gompertz-Laird, logistic, Richards, and Von Bertalanffy growth models to determine which best fits the data of the Creole chickens ( CC ). Three hundred forty-seven CC were ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
27
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 22 publications
15
27
3
1
Order By: Relevance
“…Predicted k parameters in the present study agree with those by other authors who used Von Bertalanffy models in slow-growing broilers and native creole chickens (Narinç et al 2010;Mata-Estrada et al 2020). Still these are slightly lower when compared with local breeds or slow-growing genotypes using Logistic and Gompertz models, respectively (Rizzi et al 2013;Aksoy et al 2021).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Predicted k parameters in the present study agree with those by other authors who used Von Bertalanffy models in slow-growing broilers and native creole chickens (Narinç et al 2010;Mata-Estrada et al 2020). Still these are slightly lower when compared with local breeds or slow-growing genotypes using Logistic and Gompertz models, respectively (Rizzi et al 2013;Aksoy et al 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Inflection age estimated by Logistic model in local chicken of Ghana (Osei-Amponsah et al 2014) are close to the values reported in the present study. Both sexes of Utrerana hen breed present similar results (<4 days between males and females) at the estimated inflection age, in contrast with the results obtained by Mata-Estrada et al (2020), who reported a difference between males and females of approximately 10 and 8 days for Von Bertalanffy and Logistic models. Therefore, the slaughter age for Utrerana breed must be similar in both sexes.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…One of the main differences between native turkey breeds and commercial meat-type turkey lines is the bodyweight that individuals reach, which is approximately about two or three times lower in native breeds (10 kg in Andalusian male turkey; 5-6.8 kg in Mexican backyard male turkeys and 20 kg in commercial line males) (L opez-Zavala et al, 2008;Zampiga et al 2019). These bodyweight variations are usually associated with low growth rates and worst feed conversion in native breeds (Mata-Estrada et al 2020). However, native turkey breeds have developed a genetic resistance to some diseases as a consequence of greater diversity which provides them with greater resistance than commercial lines (Kamara et al 2007;Camacho-Escobar et al 2008), since heterogeneous populations are less susceptible to viral infections (Mpenda et al 2019).…”
Section: Introductionmentioning
confidence: 99%